Visuality in the novels of Austen, Radcliffe, Edgeworth and Burney - Volz, Jessica A. (Anthem Press, 2017)
'Visuality in the Novels of Austen, Radcliffe, Edgeworth and Burney' examines the forms and functions of visuality in the novels of Austen, Radcliffe, Edgeworth and Burney. It offers new insights into vision, fiction and depiction by exploring how the visual details in women's novels published between 1778 and 1815 are more telling about gender politics than scholars have previously acknowledged.